Intracellular glycosylation and development - O'Donnell, Niall (BBA - General Subjects, 2002)
O-linked N-acetylglucosamine ( O-GlcNAc) is a highly dynamic post-translational modification of cytoplasmic and nuclear proteins. Although the function of this abundant modification is yet to be definitively elucidated, all O-GlcNAc proteins are phosphoproteins. Further, the serine and threonine residues substituted with O-GlcNAc are often sites of, or close to sites of, protein phosphorylation. This implies that there may be a dynamic interplay between these two post-translational modifications to regulate protein function. In this review, the functions of some of the proteins that are modified by O-GlcNAc will be considered in the context of the potential role of the O-GlcNAc modification. Furthermore, predictions will be made as to how cellular function and developmental regulation might be affected by changes in O-GlcNAc levels.